New Smoothing Approximations to Piecewise Smooth Functions and Applications. (4th April 2019) - Yilmaz, Nurullah; Sahiner, Ahmet
Abstract: In this study, we present a new method of smoothing to approximate piecewise smooth functions. First, we give a new definition for piecewise smooth functions. Then, we present new local and global smoothing approximations for both one dimensional and n − dimensional cases. Finally, we apply our smoothing techniques on numerical examples.